The estimation of the horizontal parameters of gravity waves by the monostatic Rayleigh Lidar - Xuanyu Zheng; Xueming Li; Qihai Chang (Scientific Reports)
Abstract Monostatic Rayleigh Lidar is mainly used for the observation of the middle atmosphere temperature and vertical activity of gravity waves. It was thought that it could not be used for the study of the gravity waves horizontal activity. Through the area integration of gravity waves that vary with time and space, it is derived that the echo signal received by the Lidar contains the horizontal wavenumber information, which proves that the monostatic Rayleigh Lidar can realize the estimation of horizontal activity of gravity waves. The feasibility is verified by using the Rayleigh Lidar observation data from the Yanqing Observatory of the Chinese Academy of Sciences. This method is suitable for the short scale horizontal activity observation of gravity waves. To improve the observation reliability of this method, it is necessary to make the Rayleigh Lidar have a reasonable divergence angle, narrow linewidth laser, and higher vertical spatial resolution.